An analysis of occupation related mental health referrals of paramillitary forces to a tertiary care hospital - Swain, Sarada Prasanna; Dash, Manoj Kumar; Pattnaik, Jigyansha Ipsita; Rath, Neelamadhab (International Journal Of Community Medicine And Public Health, 2017)
Background: The security personnel of our country including Army Personnel, C.I.S.F., Police and other security personnel bear a large amount of physical and psychological stress to maintain law and order situations at different corners of the country at different situations. To assess the Psychiatric Morbidity in C.I.S.F., the course of referrals of Para-military persons to a tertiary care hospital and to evaluate the Mental Health burden in the Para-military set up by virtue of their occupation. Methods: The study sample included all the consecutive patients referred by CISF Headquarters Hospital to the Mental Health Institute (MHI), S.C.B. Medical College, Cuttack, Odisha, from April 2015 to March 2016. The clinical information is collected from the patient and accompanying personnel from CISF or family members who accompanied the patient. The diagnosis is based on ICD-10 and the final opinion is given by the consultants of Psychiatry after final evaluation of all the reports. Results: Psychiatric assessment for job fitness (48%) was the dominant cause for referral of PMF staff to MHI. Substance abuse (alcohol) related disorders were the next common cause of referral (20%). Conclusions: Mental health burden in Para-military bases are substantial which should be taken care of in urgency basis. There is urgent need of posting of Psychiatrists with Clinical Psychologists and Psychiatric Social Worker or a team of the Mental Health Professionals should visit the paramilitary set ups regularly to look into improper diagnosis and review cases.